Long‐term survival and late complications in intensity‐modulated radiotherapy of locally recurrent T1 to T2 nasopharyngeal carcinoma. Issue 2 (27th May 2015) - Tian, Yun‐Ming; Guan, Ying; Xiao, Wei‐Wei; Zeng, Lei; Liu, Shuai; Lu, Tai‐Xiang; Zhao, Chong; Han, Fei
ABSTRACT: Background: We investigated the feasibility of reirradiation with intensity‐modulated radiotherapy (IMRT) for recurrent T1 to T2 nasopharyngeal carcinoma (NPC) by assessing long‐term survival and late complication rates. Methods: Sixty patients who had been previously irradiated were diagnosed with locally recurrent T1 to T2 NPC and underwent reirradiation with IMRT. Severe radiation toxicities were assessed. Results: The median follow‐up time was 40.0 months. The 5‐year local failure‐free survival (LFFS), distant failure‐free survival (DFFS), and overall survival (OS) rates were 85.7%, 96.1%, and 67.2%, respectively. Independent prognostic factors included primary gross tumor volume >20 cm and the presence of significant complications. The most common severe complications were headache (31.6%), mucosal necrosis (30.0%), cranial neuropathy (25.0%), and temporal lobe necrosis (21.6%). Thirty‐nine patients (65.0%) developed at least one severe complication and 18 patients died as a result. Conclusion: Excellent disease control can be achieved by reirradiation with IMRT for recurrent T1 to T2 NPC. However, the main challenge remains severe late complications. © 2015 Wiley Periodicals, Inc. Head Neck 38: 225–231, 2016